The Everyday Life of ‘Socially Dangerous Children’ in the Postwar Period - Korenyuk, Valentina M.; Suslov, Andrey B. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2018)
This paper considers the everyday life of children whose parents had been politically repressed. Mostly, the authors focus on materials from Perm region, relying on the methods and approaches of everyday history. The analysis is based on legislative regulations, archival documents, such as NKVD files, and memoirs, based on the oral accounts of witnesses. In this category, the authors focus on the ones that are both typical and emotional. The article considers the living conditions of the social group in question. The difficulties they faced were common for all Soviet people, however, their social status could exacerbate them. The authors refute the idea that during the postwar years, all children equally regarded the period as sombre, as much depended not only on the social status of the children in the local community but also on the political situation in the country. The authors single out obstacles the children whose parents had been repressed were facing, especially in the educational sphere. They describe the atmosphere of suspicion they lived in. Additionally, the authors pay attention to the children’s mental state, as their parents were deprived of their rights, and demonstrate that they experienced a constant lack of comfort, because society was prejudiced against them as “enemies of the people”.